The Lancet Weight Determines Wheal Diameter in Response to Skin Prick Testing with Histamine. - Hjalte H Andersen; Anna Charlotte Lundgaard; Anne S Petersen; Lise E Hauberg; Neha Sharma; Sofie D Hansen; Jesper Elberling; Lars Arendt-Nielsen (PLoS ONE)
Background Skin prick test (SPT) is a common test for diagnosing immunoglobulin E-mediated allergies. In clinical routine, technicalities, human errors or patient-related biases, occasionally results in suboptimal diagnosis of sensitization. Objective Although not previously assessed qualitatively, lancet weight is hypothesized to be important when performing SPT to minimize the frequency of false positives, false negatives, and unwanted discomfort. Methods Accurate weight-controlled SPT was performed on the volar forearms and backs of 20 healthy subjects. Four predetermined lancet weights were applied (25 g, 85 g, 135 g and 265 g) using two positive control histamine solutions (1 mg/mL and 10 mg/mL) and one negative control (saline). A total of 400 SPTs were conducted. The outcome parameters were: wheal size, neurogenic inflammation (measured by superficial blood perfusion), frequency of bleeding, and the lancet provoked pain response. Results The mean wheal diameter increased significantly as higher weights were applied to the SPT lancet, e.g. from 3.2 ± 0.28 mm at 25 g to 5.4 ± 1.7 mm at 265 g (p<0.01). Similarly, the frequency of bleeding, the provoked pain, and the neurogenic inflammatory response increased significantly. At 265 g saline evoked two wheal responses (/160 pricks) below 3 mm. Conclusion and clinical relevance The applied weight of the lancet during the SPT-procedure is an important factor. Higher lancet weights precipitate significantly larger wheal reactions with potential diagnostic implications. This warrants additional research of the optimal lancet weight in relation to SPT-guidelines to improve the specificity and sensitivity of the procedure.